EFL Students’ Perceptions Towards the Use of Grammarly Application in Learning Writing Skills - Khonirin, Fara Anandita; Roslaini, Roslaini (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2024)
This study explores the perceptions of English as a Foreign Language (EFL) students towards the use of the Grammarly application in improving their writing skills. Conducted at the University of Muhammadiyah Prof. Dr. Hamka Jakarta, the research involved 120 students. A quantitative approach was used with survey administered a closed-ended questionnaire with 20 items. Data were collected using Google Forms and the analysis was carried out using a 5-Likert Scale, with averages generated in Microsoft Excel. The study eval____uates a students' views regarding the efficacy, usability, and overall impact of Grammarly on their writing. The findings indicate that while Grammarly is perceived as a useful tool for identifying grammatical errors and enhancing writing quality, students also highlighted concerns about over-reliance on the tool, which could affect their attentiveness to writing without the software. Despite these concerns, the majority of participants reported improved writing confidence and skills. The study concludes that Grammarly can be an effective supplementary tool in EFL writing instruction, provided its limitations are addressed and it is used in conjunction with traditional teacher feedback